Taking risks to play it safe: value capture strategies of architectural firms - Bos -de Vos, Marina; Volker, Leentje; Wamelink, Hans (A+BE | Architecture and the Built Environment, 2018)
Project-based firms have to capture value from the projects in which they engage. This can be a challenging process, as firms need to reconcile project goals and organizational goals while attempting to avoid value slippage. Drawing on case-based interviews with architects and clients, this research reveals how architectural firms used the strategies of postponing financial revenues in a project, compensating for loss of financial revenues across projects and rejecting a project to capture value. The study contributes to the literature on project business by showing that firms will sometimes risk or accept slippage of financial value yet counteract the potential slippage of professional value in projects to enhance the overall benefits for the firm. These insights help to advance the research on value capture by project-based firms and can be used by managers to identify and overcome value capture difficulties at project and firm levels.